The dirt diary - Staniszewski, Anna (Naperville, Illinois : Sourcebooks, Jabberwocky, 2014)
After her parents' divorce, eighth-grader Rachel Lee joins her mother's new housecleaning business, which has her scrubbing bathrooms in her more popular classmates' homes and learning useful secrets.
About the AuthorBack Cover.
Print version record.
Keywords: Diaries -- Juvenile fiction; Secrecy -- Juvenile fiction; Popularity -- Juvenile fiction; Schools -- Juvenile fiction; House cleaning -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Single-parent families -- Juvenile fiction; Diaries -- Fiction; Secrets -- Fiction; Popularity -- Fiction; Schools -- Fiction; House cleaning -- Fiction; Dating (Social customs) -- Fiction; Single-parent families -- Fiction; Diaries; House cleaning; Popularity; Electronic books; Juvenile works